Factors related to employee burnout : Organizational Behavior Review - Suci Nabila Putri; Chichi Andriani (Human Resource Management Studies, 2021)
This study aims to analyze: (1) The influence of conscientiousness personality dimension on burnout in Prison Class II B Lubuk Basung employees. (2) The influence of neuroticism personality dimension on burnout on Prison Class II B Lubuk Basung employees. (3) The influence of quality of work life on prison officers class II B Lubuk Basung. (4) Workload effect on burnout on Prison Officers Class II B Lubuk Basung. This research is descriptive causative research. The population in this study is all employees of Class II Prison B Lubuk Basung which amounts to 40 people. Sampling technique in this study is total sampling technique. The study was analyzed with multiple linear regression analysis using spss 24.0 program. The results of this study found that: (1)The dimension of personality conscientiousness negatively affects burnout in prison employees Class II B Lubuk Basung (2) Dimension personality neuroticism positively affect burnout in prison workers Class II B Lubuk Basung . (3) The quality of working life negatively impacts burnout in Prison Class II B Lubuk Basung (4) Workload is very positive to burnout in Class II B Lubuk Basung Prison employees.